Natural resources management using fly ash in South Kalimantan, activated with acid and alkali as an adsorbent to reduce metal cations from acid mine drainage - Ermiyati, Ana; Indrayatie, Eko Rini; Santoso , Uripto Trisno; Nugroho , Agung (Journal of Degraded and Mining Lands Management, 2025)
Coal in South Kalimantan is widely used in industry and the Steam Electric Power Center (PLTU) as boiler fuel for power generation. Fly ash is a waste produced by about 80% of coal combustion. Fly ash solid waste, if not handled properly, can cause environmental pollution in water, air, and soil. The utilization of environmentally friendly fly ash is a crucial issue in reducing the environmental burden. One of them is by utilizing fly ash as an adsorbent. This study examines the characteristics and effectiveness of fly ash in South Kalimantan as an adsorbent for Fe, Mn, and Cd metal cations in acid mine drainage. Fly ash used is fly ash without activation (FA), activated fly ash with HCl 1 M (HFA), and activated with NaOH 1 M (NaFA).The three types of adsorbents (FA, HFA, and NaFA) have characteristics that include a dominant content of silica oxide (SiO2),  alumina oxide (Al2O3), and iron oxide (Fe2O3), as well as spherical particles. NaFA has the largest surface area of 26.945 m2/g, FA 9.499 m2/g, and HFA 21.994 m2/g. NaFA has the highest absorption with optimum Fe of 99.9%, Mn of 94.8% and Cd of 99.9%. NaFA is more effective in reducing Fe metal ions compared to FA and HFA at an adsorbent mass of 10 g. Likewise with the metal ions Mn and Cd, NaFA is most effective in reducing both metal ions at an adsorbent mass of 30 g.